1996
DOI: 10.1034/j.1600-0501.1996.070106.x
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for tactile sensitivity perceived with dental implants remain unchanged during healing phase of 3 months

Abstract: The aim of the present study was to determine the tactile pressure thresholds perceived with dental implants during a three-month healing phase following implant placement (osseointegration phase). The absolute threshold of tactile perception was measured in a group of patients 1 week, 1, 2 and 3 months following implant placement (ITI Dental Implant System, Straumann AG, Waldenburg, Switzerland). Contralateral and neighbouring teeth were measured at the same time. For determination of the axial forces exerted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 0 publications
1
26
0
1
Order By: Relevance
“…As far as active tactile sensibility is concerned, it could be shown that the interocclusal perception sensibility of single‐tooth implants when occluding against natural antagonists and of the remaining natural dentition are equivalent ( P < 0.01, power >80%) 14 . In passive tactile sensibility studies, the implants were clearly less sensitive than the teeth selected for comparison; the values for passive tactile capability were higher by a factor of 8 to 10, and in some cases they were 50 times higher 15–17 . Very small static pressures cannot be felt through osseointegrated implants, but greater static and dynamic loads (= vibrations) in axial and horizontal direction can be felt 18 .…”
Section: Introductionmentioning
confidence: 99%
“…As far as active tactile sensibility is concerned, it could be shown that the interocclusal perception sensibility of single‐tooth implants when occluding against natural antagonists and of the remaining natural dentition are equivalent ( P < 0.01, power >80%) 14 . In passive tactile sensibility studies, the implants were clearly less sensitive than the teeth selected for comparison; the values for passive tactile capability were higher by a factor of 8 to 10, and in some cases they were 50 times higher 15–17 . Very small static pressures cannot be felt through osseointegrated implants, but greater static and dynamic loads (= vibrations) in axial and horizontal direction can be felt 18 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, tactile perception of natural tooth abutments was shown to be significantly higher (8.8‐fold) than that demonstrated for implant abutments (Hämmerle et al 1995). These increased thresholds for tactile perception in implants were established already after one week of healing and remained unchanged during the entire healing period of tissue integration (3 months) of the implants (Keller et al 1996). Hence, for reasons of chewing comfort the incorporation of natural teeth as abutments in otherwise implant‐supported reconstructions may also be practiced.…”
mentioning
confidence: 97%
“…After being restored with an implant‐supported prosthesis, patients seem to function well, perceiving mechanical stimuli exerted on osseointegrated implants in the jawbone . In patients followed up after implant placement, a noticeable improvement in tactile function with dental implants following a 3‐month healing period has been observed, potentially indicating that the feedback pathway to the sensory cortex is partly restored with a hypothetical representation of the prosthesis in the sensory cortex, allowing a more appropriate modulation of the motor neuron pool, and leading to a more natural functioning and avoiding overload …”
Section: Resultsmentioning
confidence: 99%